Prinsip Dan Unsur-Unsur Komunikasi Dalam Prespektif Al -Quran - Tomi Hendra; Peri Musliadi (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2019)
Abstract: This study uses a type of library research (Library Research), namely by reading works related to the issues to be studied. The author will examine the principle of communication in the perspective of the Qur'an in terms of the elements of communication using the